First passage time distribution of active thermal particles in potentials - Walter,B; Pruessner,G; Salbreux,G (Physical Review Research, 2021)
We introduce a perturbative method to calculate all moments of thefirst-passage time distribution in stochastic one-dimensional processes whichare subject to both white and coloured noise. This class of non-Markovianprocesses is at the centre of the study of thermal active matter, that isself-propelled particles subject to diffusion. The perturbation theory aboutthe Markov process considers the effect of self-propulsion to be small comparedto that of thermal fluctuations. To illustrate our method, we apply it to thecase of active thermal particles (i) in a harmonic trap (ii) on a ring. Forboth we calculate the first-order correction of the moment-generating functionof first-passage times, and thus to all its moments. Our analytical results arecompared to numerics.